Growth And Results of Some Microgreens of Order Caryophyllales on Different Plant Media - Lanna Reni Gustianty; Zulia, Cik; Muhammad Yoga (Kirana Publisher (KNPub), 2023)
The research was conducted at the Tissue Culture Laboratory, Faculty of Agriculture, Asahan University, from March 2022 to April 2023. The aim of this study was to determine the growth and yield of several microgreens of the order Ceryophyllales on different planting media. The design used was a factorial Completely Randomized Design (CRD), with 1 treatment factor: the first factor was: Growing Media (M) (M) consisted of M1 = rockwool, M2 = cocopeat, M3 = vermiculite. The observed variables consisted of: percentage of live seeds, number of seed germinations, plant height, number of leaves, fresh weight.The results showed that the treatment of several microgreens of the order (O) caryophyllales where the red spinach (O2) treatment gave the highest percentage of survival could have a real effect on the percentage of live seeds 0.82%, the number of seed germinations 13.89%, plant height 1.48% , number of leaves 1.51%, and the treatment of basil plants was not significantly different at 0.56% fresh weight. The treatment of different planting media (M) where the treatment of vermiculite growing media gave the highest percentage of survival could have a significant effect on the percentage of live seeds 0.79%, the number of seed germinations 11.22%, plant height 1.44%, number of leaves 1.45% , and the treatment of cocopeat plant media was not significantly different at 0.52% fresh weight. The interaction of several microgreens of the order Caryophyllales and different growing media had no significant effect on the percentage of live seeds, the number of seed germinations, plant height, number of leaves, fresh weight.